Misresponse to Survey Questions: A Conceptual Framework and Empirical Test of the Effects of Reversals, Negations, and Polar Opposite Core Concepts - Baumgartner, Hans; Weijters, Bert; Pieters, Rik (Journal of Marketing Research, 2018)
The authors propose a conceptual framework of misresponse to multi-item scales in surveys in which misresponse to items that are reversed relative to other items (reversal misresponse) is differentiated from misresponse to items that are negated (negation misresponse) and from misresponse to items whose core concept is the opposite of the core concept in regular items (polar opposite misresponse). The framework specifies two broad mechanisms to account for the three forms of misresponse: lack of motivation to process items in detail (“inattention”) and lack of ability to comprehend items accurately (“difficulty”). The authors propose a procedure to identify potential misresponse effects on the observed item responses and factor loadings, and they report two empirical studies to test the framework; the second study uses eye movement recordings to examine the underlying process. The findings reveal that polar opposite, reversed, and negated items contribute to misresponse to varying degrees and that difficulty rather than inattention may be a more potent cause of misresponse in surveys than has traditionally been acknowledged.